Yeast as a Potential Vehicle for Neglected Tropical Disease Drug Discovery. (January 2015) - Denny, P.W.; Steel, P.G.
High-throughput screening (HTS) efforts for neglected tropical disease (NTD) drug discovery have recently received increased attention because several initiatives have begun to attempt to reduce the deficit in new and clinically acceptable therapies for this spectrum of infectious diseases. HTS primarily uses two basic approaches, cell-based and in vitro target-directed screening. Both of these approaches have problems; for example, cell-based screening does not reveal the target or targets that are hit, whereas in vitro methodologies lack a cellular context. Furthermore, both can be technically challenging, expensive, and difficult to miniaturize for ultra-HTS [(u)HTS]. The application of yeast-based systems may overcome some of these problems and offer a cost-effective platform for target-directed screening within a eukaryotic cell context. Here, we review the advantages and limitations of the technologies that may be used in yeast cell–based, target-directed screening protocols, and we discuss how these are beginning to be used in NTD drug discovery.